(untitled) (AWKA JOURNAL OF ENGLISH LANGUAGE AND LITERARY STUDIES, 2025)
L’article examine le rôle essentiel de l’intonation dans l’organisation prosodique du français, tant au niveau syntaxique que pragmatique. Il propose une revue systématique des principaux modèles théoriques de l’intonation en français, notamment autosegmentaux, métriques et perceptifs, en s’appuyant sur les travaux de chercheurs tels que Hualde, Rosen, Bacelar et Cruse. Une analyse comparative permet d’évaluer la pertinence de ces modèles pour décrire la variété des contours intonatifs de l’oral. L’étude aborde aussi leurs applications pratiques, en particulier dans l’enseignement du FLE et les technologies de reconnaissance vocale. En mettant en lumière les points de convergence et de divergence entre ces approches, l’article fournit un cadre de référence utile aux chercheurs, enseignants et concepteurs d’outils linguistiques. The article explores the essential role of intonation in the prosodic organization of French, affecting both syntactic structure and the transmission of pragmatic information. It presents a systematic review of the main theoretical models of French intonation - including autosegmental, metrical, and perceptual approaches - drawing on the work of researchers such as Hualde, Rosen, Bacelar, and Cruse. A comparative analysis evaluates how effectively these models account for the diversity of intonational patterns in spoken French. The study also examines practical applications, particularly in the teaching of French as a foreign language (FLE) and in speech recognition technologies, both of which must handle complex prosodic parameters. By highlighting the convergences and divergences among these approaches, the article offers a useful framework for researchers, educators, and developers of linguistic digital tools.